ICMS ecológico em Sergipe: uma proposta de incentivo à implementação de políticas públicas ambientais - Franca, Thamima Siquara Sobral (2017)
The effects of environmental degradation compromise the quality of people’s life, restricting their right to enjoy an ecologically balanced environment. Due to the current scenario, where many environmental problems require new measures and solutions, an effective action of the public authority is necessary, to meet the demands of society, through public environmental policies. The purpose of this research was to propose a model for the implementation of Ecological ICMS in Sergipe, in order to stimulate the execution of public environmental policies by the local municipalities. Specifically, this study sought to examine the environmental criteria for the transfer of ICMS revenue used by the states that have already embraced this mechanism, to analyze environmental management indicators of the municipalities of Sergipe and to demonstrate how these indicators are presented in the context of an Ecological ICMS model for the state of Sergipe. Considering the low occurrence of scientific studies that approach the theme concerning the state of Sergipe, the methodological procedure used was exploratory, with a qualitative approach. The first stage of the data collection consisted of the analysis of the environmental criteria applied for distribution of the ICMS revenue, according to the state laws of the Green ICMS. For the second part, indicators of institutional capacity and environmental planning were selected from the IBGE's Basic Municipal Information Survey. The results showed that, given the low quality of environmental management of the local municipalities of Sergipe, it is evident the need for an instrument such as the Ecological ICMS, which works as an incentive for the embracing of public environmental policies, focused on promoting sustainable development and improving quality of life of population. In conclusion, this research culminated in the proposition of an Ecological ICMS model for the state of Sergipe.